Penerapan Metode Autoregressive Integrated Moving Average (ARIMA) pada Peramalan Data Inflasi di Kabupaten Cilacap - Qathrunnada Salsabila; Suwanda (Bandung Conference Series: Statistics, 2024)
Abstract. In the general and production subsection at the Central Statistics Agency of Cilacap Regency with tasks such as data collection, data recapitulation, entering survey documents conducted, and editing the Cilacap book in figures for 2023. In this study, the author wants to forecast inflation in Cilacap Regency from January 2018 to July 2023 to find out whether inflation at the end of 2023 will be higher than the previous year. This analysis uses the ARIMA (Autoregressive Integrated Moving Average) method with the parameters obtained, namely ARIMA (2,1,1). So it can be concluded that inflation that occurs in the next five months has increased and decreased from the previous year, namely 0.09% in August 2023; -0.04% in September 2023; -0.02% in October 2023; 0.03% in November 2023; -0.00% in December 2023. Abstrak. Pada subbagian umum dan produksi di Badan Pusat Statistika Kabupaten Cilacap dengan tugas-tugas seperti pengumpulan data, merekap data, mengentry dokumen survey yang dilakukan, serta mengedit buku Cilacap dalam angka 2023. Dalam penelitian ini penulis ingin melakukan peramalan inflasi di Kabupaten Cilacap dari bulan Januari tahun 2018 sampai bulan Juli tahun 2023 untuk mengetahui apakah inflasi di akhir tahun 2023 akan lebih tinggi dari bulan tahun sebelumnya. Analisis ini menggunakan metode ARIMA (Autoregressive Integrated Moving Average) dengan parameter yang diperoleh yaitu ARIMA (2,1,1). Maka dapat disimpulkan bahwa inflasi yang terjadi lima bulan kedepan mengalami naik dan turun dari tahun sebelumnya yaitu sebesar 0.09% dibulan Agustus 2023; -0.04% di bulan September 2023; -0.02% dibulan Oktober 2023; 0.03% dibulan November 2023; -0.00% dibulan Desember 2023.